Problem Kompatibilitas dan Stabilitas Pencampuran Sediaan Intravena Pada Pasien Anak di RSUP Dr. Sardjito - Rahmawati, Reza; Rahmawati, Fita; Azhar Syed Sulaiman, Syed (Jurnal Farmasi (Journal of Pharmacy), 2018)
Inappropriate preparation and administration intravenous drug may caused harm and therapeutic failure for the patient. In pediatric patient, intravenous drug administration is very critical because of poor venous access especially when simultaneously drug administration required which is can lead into incompatibilities occurence. Errors in intravenous drug administration can affect the drug stability also. Therefore, this research aims to investigate the prevalence of incompatibility and stability in pediatric hospitalized patient. This research was done with prospective study at RSUP Dr. Sardjito in Pediatric Intensive Care Unit (PICU) and pediatric ward from November-December 2017. Data collection was done with pediatric hospitalized patient that used at least 1 intravenous drug. Compatibility and stability were analyzed using standard reference Handbook of Injectable Drugs and other references. A total pediatric hospitalized patients are 75 patients, 34 patients are from PICU and 41 patients are from pediatric ward. Intravenous drugs used are 49.1% with the mean of intravenous drugs are 3.3 drugs/patient. Compatible drug combinations are 73.3% and unknown are 26.3%. There are no incompatible drug combination found in this research. Stability problems were found in 3 drug combination that administered by continuous infusion.